The effect of policyholders' rationality on unit-linked life insurance contracts with surrender guarantees - Jing Li; Alexander Szimayer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
We study the valuation of unit-linked life insurance contracts with surrender guarantees. Instead of solving an optimal stopping problem, we propose a more realistic approach accounting for policyholders' rationality in exercising their surrender option. The valuation is conducted at the portfolio level by assuming the surrender intensity to be bounded from below and from above. The lower bound corresponds to purely exogenous surrender and the upper bound represents the limited rationality of the policyholders. The valuation problem is formulated by a valuation PDE and solved with the finite difference method. We show that the rationality of the policyholders has a significant effect on average contract value and hence on the fair contract design. We also present the separating boundary between purely exogenous surrender and endogenous surrender. This provides implications on the predicted surrender activity of the policyholders.
Keywords: G13; G22; C65; 330; Unit-linked life insurance contracts; surrender guarantee; limited rationality; fair contract analysis; Lebensversicherung; Investmentfonds; Rückvergütung; Bewertung; Vertrag; Gerechtigkeit; Theorie